2015
DOI: 10.1038/aps.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Novel chemical scaffolds of the tumor marker AKR1B10 inhibitors discovered by 3D QSAR pharmacophore modeling

Abstract: Aim: Recent evidence suggests that aldo-keto reductase family 1 B10 (AKR1B10) may be a potential diagnostic or prognostic marker of human tumors, and that AKR1B10 inhibitors offer a promising choice for treatment of many types of human cancers. The aim of this study was to identify novel chemical scaffolds of AKR1B10 inhibitors using in silico approaches. Methods: The 3D QSAR pharmacophore models were generated using HypoGen. A validated pharmacophore model was selected for virtual screening of 4 chemical data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The RMSD of protein backbone atoms and potential energy profiles obtained from the simulations indicate the overall stability of the simulated systems ( Supplementary Fig. S1 ) [ 39 ]. The RMSD values were between 0.15 nm to 0.36 nm for all the protein-drug complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RMSD of protein backbone atoms and potential energy profiles obtained from the simulations indicate the overall stability of the simulated systems ( Supplementary Fig. S1 ) [ 39 ]. The RMSD values were between 0.15 nm to 0.36 nm for all the protein-drug complexes.…”
Section: Resultsmentioning
confidence: 99%
“…The RMSD values were between 0.15 nm to 0.36 nm for all the protein-drug complexes. Varying RMSD values at the initial few nanoseconds of the simulations indicate the initial adjustment of ligands at the active site of SARS-CoV-2 M pro [ 39 , 40 , 41 ]. The analysis indicated that each system reached steady-state after convergence, and RMSD values remained within the acceptable value of <0.3 nm except the M pro -Atorvastatin complex (0.36 nm) during the 50 ns simulation run [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The molecular dynamics (MD) simulations of POP in a complex with inhibitors and final hit compounds were carried out with CHARMM27 all-atom force field using Groningen machine for chemical simulations (GROMACS 4.5.7) software 55 , as previously described 56 58 . The topology files for all ligands were generated using the SwissParam program 59 .…”
Section: Methodsmentioning
confidence: 99%
“…The structure has a depth of resolution 2.8 Å and contains 216 amino acids, ligand 3, 5-dinitrocatechol (DNC), cofactor S-adenosyl L- methionine (SAM), and magnesium ion (Mg +2 ). Removal of water molecules, energy minimization (Kumar et al, 2015; Modi et al, 2016) were performed with the help of the standard steepest decent conjugate method in YASARA (Parmar, Patel, Highland, Pandya, & George, 2016). The 36 ligands from ZINC database (Irwin et al, 2012) were docked in the place of DNC, located at the binding site of COMT.…”
Section: Methodsmentioning
confidence: 99%